Pendampingan Masyarakat Sebagai Fasilitator Dalam Memandu Kegiatan Musrenbang Tingkat Kelurahan - Erialdy; Tb. Yudi Muhtadi (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
The importance of strengthening community capacity related to innovation in sustainable development planning policies in development management is an effort and strategy in reconstructing the process of socio-cultural, economic and political change towards community welfare that is designed on a bottom up or grassroots basis. Musrenbang Kelurahan is a stakeholder communication forum to propose, prioritize and agree on proposals from the results of community meetings at the Rukun Warga (RW) level, there are efforts to solve problems collectively, through a learning process among stakeholders, a process of interaction, discussion and accommodation. Participation is the will of the community to support development programs in planning, implementing, preserving and developing them in the form of cooperation between the government as the policy holder and the community on the other hand as the party who feels the impact of the development policy directly. The role of the Musrenbang Facilitator or Guide is indispensable in managing the Musrenbang stages, at the meeting / deliberation forum activities and arranging the stages and steps of the overall Musrenbang process.